Acid-base balance and nitrogen excretion in invertebrates : mechanisms and strategies in various invertebrate groups with considerations of challenges caused by ocean acidification /: mechanisms and strategies in various invertebrate groups with considerations of challenges caused by ocean acidification. ([2017]) - Unknown
No abstract available